Adaptive water resource management in the South Indian Lower Bhavani Project Command Area - Lannerstad, Mats; David, S. (International Water Management Institute, 2009)
This report explores the theory and practice of Adaptive Water Management (AWM) based on a detailed field study in the Lower Bhavani Project (LBP) in the South Indian state of Tamil Nadu. A five-step framework is used to analyze the extent to which AWM is practiced and how it could be improved. The analysis shows that the LBP system has increasingly fulfilled the criteria of a complex adaptive system over the years. The main uncertainty factor, rainfall variability, has been considered in a stepwise way during the system change cycles and has been included in the LBP system design. The study shows that in spite of contending with an imperfect irrigation system design and intense competition for water resources, water resource managers and farmers are able to adapt and continue to reap benefits from a productive agricultural system.